Botulinum toxins in clinical aesthetic practice - Benedetto, Anthony V. (Series in cosmetic and laser therapy, 2011)
This second edition retains all the features that made its predecessor so successful, including detailed anatomic drawings, a review of the different formulations available, and specimen forms. This edition has been revised and updated throughout and features additional new material on medico-legal considerations and psychological and cultural factors that may affect the intentions of patients and the results that can be achieved.